The influence of friction on sports surfaces in turning movements - Dura, J. V.; Hoyos, J. V.; Martinez, A.; Lozano, L. (Sports Engineering, 1999)
A 180° turning movement was performed over five surfaces with different coefficients of friction measured with the method defined in the standard DIN18032-2. Two different phases were found: the braking and the starting phase. The results show that people adapt their movement, increasing time and knee flexion angle during the braking phase. Considering the time taken to perform the movement as a performance parameter, it was found that there is a compensation between the two phases that reduces the differences in times and causes the global performance to be similar on the different surfaces. In this manner, low friction coefficients are better because muscle stress and torque in joints are reduced.